Heavy-Loaded Components Quality Assurance by Means of Non-Destructive Testing; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Kroening H. M. V. A. Hans Michael Wilhelm Adolf (Sensors, Measurements and Non-Destructive Control, 2014)
Title screen